A new natural hybrid of Scutellaria (Lamiaceae) from Turkey - Çi̇çek Mehmet; Yaprak, Ahmet Emre (Phytotaxa, 2011)
Scutellaria ×ketenoglui M.Cicek & Yaprak, a natural hybrid between S. tortumensis and S. sosnowskyi subsp. sosnowskyi is described as new to science from northeastern Anatolia, Turkey, and illustrated. The morphological characteristics of S. ×ketenoglui are compared with those of its parents.